THE ENGLISH LEARNING QUALITY DURING PANDEMIC COVID-19 OF STUDENTS AT SMP NEGERI 1 TELUK DALAM - Loi, Mega Putriani Foni Serni; Laia, Rebecca Evelyn; Ndraha, Lies Dian Marsha (Universitas Nias Raya, 2022)
This research aimed to know how The English learningQuality during pandemic of students at SMP Negeri 1 Telukdalam. The total participants was nine participants; three participants from seventh grade, three participants from eigth grade and three participants from ninth grade. The research is used qualitativeresearch approach which used descriptive type of research to describe the English learning quality by using seven indicators of learning quality by Departemen Pendidikan Nasional. The technique of data collection in the research were interview the students and English teachers and observation using field note inEnglish teaching learning process in the class. The result shows that the students in SMP Negeri 1 Teluk Dalam was unfulfilled the learning quality indicators. There are three indicators that was unfulfilled, the indicators were Student’s Activity indicator, Material indicator, and Students’ outcome indicator. Based onthe result of the research, it can be concluded that the English learning quality during pandemic covid-19 of students at SMP Negeri 1 TelukDalam is unfulfilled in some indicators. The researcher suggest that, the english teachers should be able to explorate the class in online or offline class to improve the learning toreach the indicators learning quality, and also for the students should be able to adapt with any situation in learning even in online or offline class.